Effect of knowledge sharing on academic performance of postgraduate students of private Universities in Kenya - Onditi, Walter Ouma; Nzioki, Susan; Murithi, Simon (International Journal of Professional Practice, 2023)
Knowledge Management (KM) practices have been used across the globe to measure organization performance. However, gaps still exist on the effects of knowledge sharing (KS) on academic performance of students in institutions of higher learning. Based on Human Capital Theory, the study attempted to bridge this information gap by assessing the effect of KS on academic performance of postgraduate students of private universities in Kenya. Descriptive cross-sectional survey design was used. A sample of 370 respondents was drawn from a population of 12,919 postgraduate students and faculty/department heads. Stratified random sampling technique was used to obtain the sample. The findings indicated a 27.8% variation in postgraduate academic performance; KS had a strong significant and positive correlation (r=0.485, p<0.001), and significant partial factor effect (β = 0.455, p=0.000) on postgraduate academic performance in private universities. The conclusion was that KS had significant effect on postgraduate academic performance in private universities, Kenya. The study recommended management and leadership of private universities to strengthen KS application and methodologies as a measure to enhance academic performance. It also recommended that similar efforts be extended to public universities so as to ensure comprehensive contribution of KS to learning outcomes in the Kenyan education sector.